Decolonization of Brazil's border with Paraguay: the cross-border Guarani and Kaiowá peoples and the multi/transterritoriality of the struggle for tekoha - Mondardo, Marcos (Instituto de Estudios Internacionales, 2021)
This article analyzes the issue of the struggle for the tekoha of the Guarani and Kaiowá peoples from a geographical perspective, and with respect to the movement to decolonize the border between Brazil and Paraguay. The research methodology was outlined using a qualitative and quantitative approach. In addition to the selection of native concepts, a bibliographic survey was used and field work was also carried out. Multi-transterritoriality is a form of territorial displacement that coordinates networks of political, economic, and ethnic relationships. This allows groups of Guaraní to fight for the demarcation of the tekoha on both sides of the border, thus favoring the effective movement of this group between territories and activating numerous indigenous territorialities.